FAKTOR-FAKTOR PENYEBAB TERJADINYA PERSAINGAN USAHA TIDAK SEHAT DI INDONESIA - Andos Rewindo Sirait (JURNAL JUSTIQA, 2019)
The development of the business world can not be denied is influenced by various factors both internal and external, factors. The development of the business world both past, present and even to the future of the role of businessmen or entrepreneurs in running a business or business. The rapid development of the business world and with the high demand (demand) market or a goods (commodities) to create and encourage businesses to conduct innovation continue - constantly adapted to the needs of consumers, so that consumers do not run and can make the market become sluggish. Unhealthy competition was not without reason, but there are certain reasons that led to the unfair competition. The occurrence of unfair business competition has certainly done by the business either together or individually to determine or make a favorable state business operators themselves. Factors that lead to unhealthy competition can occur due to a favorable circumstances, businesses and take advantage of the sake and the benefit of the business operators, although it will eventually hurt other businesses. Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition is not only designed to protect consumers, but other businesses that did not participate or was involved in the unfair competition. The law prohibits businesses that intend to unfair competition that does not do any harm in the form of other businesses. So the purpose of this law to protect businesses that wish to compete in a healthy manner can be protected.